Application of Islamic Law in Economic Dispute Resolution in the Digital Era - Ghina, Ghina Raudatul Jannah; Syukri, Khairiadi Syukri (Alhamdulillah : Jurnal Agama Islam, 2024)
Islamic Religious Education plays a very important role in shaping the character of the millennial generation, especially in facing the challenges of globalization and rapid technological developments. The millennial generation is often faced with problems of moral crisis and self-identity due to the influence of more dominant foreign cultures. Therefore, Islamic religious education is expected to provide a solid foundation in shaping a character that is noble, honest, and responsible. This study aims to examine how Islamic religious education can contribute to the formation of the character of the millennial generation, by emphasizing the importance of integrating religious values in everyday life. The methods used in this study were literature reviews and interviews with a number of educators and students involved in Islamic religious education. The results of the study show that Islamic religious education provided intensively can help the millennial generation build a stronger character, both in personal and social aspects. In addition, Islamic religious education can also increase awareness of the importance of ethics and morals in the increasingly developing digital life. Thus, Islamic religious education can be an important factor in creating a millennial generation that is not only intellectually intelligent, but also moral and has high integrity.